Sedentary time and perceived neighborhood environment in adolescents aged 12-17 years - Tais Taiana Sarabia; Mariana Silva dos Reis; Priscila Bezerra Gonçalves; Rodrigo Siqueira Reis (Universidade Federal de Santa Catarina, 2018)
The environment around the residence could contribute to attenuate or increase time spent in sedentary activities, and in low energy expenditure activities (1.5 METS) in adolescents. The aim of this study was to analyze the association between sedentary time and perceived neighborhood environment in adolescents aged 12-17 years living in southern Brazil. This was an observational cross-sectional study conducted from August 2013 to May 2014, with a sample of adolescents (12-17 years), recruited from 32 census tracts in Curitiba, Brazil. All census tracts were selected according to walkability and income characteristics. Perceived environment was assessed through the NEWS-Y questionnaire, and sedentary time along seven days was obtained through accelerometers (GT1M, GT3x and GT3x+). Linear regression models were used to test the associations, and included age, nutritional status, socioeconomic level and education level as confounding variables. All analyses were performed considering p-value <0.05 through SPSS software 20.0. The analytical sample included 364 adolescents (girls=50.5%; mean age=14.7, SD=1.7) with valid accelerometry data, showing on 489.6 minutes/day (SD=99.5) spent in sedentary time activities. After adjusting for confounding variables, only the perception of places for walking and cycling remained associated with sedentary time for both boys (B=-23.402, p=0.016) and girls (B=-15.572; p=0.079). Perception of places for walking and cycling has an inverse relationship with sedentary time among adolescents living in places with extremes of walkability and income.